Imports of Raw Materials, Spillover of Foreign Investment and Technical Efficiency of Indonesia's Manufacturing Industry Exports - Muslikhati, Muslikhati (UPT Penerbitan Universitas Jember, 2025)
This research uses data from 15 Indonesian manufacturing industries during 6 years. It examines two main points: first, whether the manufacturing industry in Indonesia is technically efficient; second, whether imports of raw materials, foreign investment spillovers, and technical efficiency influence export tendencies. The study employs the Stochastic Frontier Analysis method to assess technical efficiency and logit models to estimate the effects of raw material imports, foreign investment spillovers, and technical efficiency on export efficiency. The estimation results show that the Indonesian manufacturing industry is not yet technically efficient. Additionally, the logit model results reveal that raw material imports positively affect exports, horizontal spillovers negatively affect exports, and technical efficiency positively affects exports. We recommend that the government (a) encourage the development of competitive domestic upstream industries to increase domestic added value in the manufacturing industry; (b) cooperate with other countries for technology transfer; (c) enhance Research and Development (R&D) activities within companies; and (d) increase FDI inflows to boost export propensity.